Integration of Hadith Values in the Islamic Education Curriculum - Acep Dani Ramdani; Nur Ainiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the urgency and relevance of integrating hadith values into the educational curriculum. As the second source of law after the Qur'an, the hadith plays a crucial role in shaping students' character, morals, and ethics. The study employed qualitative methods with a literature review and case study approach. The results indicate that integrating hadith values into the curriculum enhances students' understanding of Islamic teachings, shapes their character, and enriches the moral and ethical content of education. The most important aspect of implementing hadith as a source of learning material is the development of good character, in addition to assisting students in academic aspects. The integration of hadith values into educational science is not merely the addition of religious material, but rather a comprehensive philosophical, pedagogical, and practical transformation. Teachers and education personnel play a crucial role in ensuring that the integration of hadith values is carried out systematically and structured.